Zinc oxide nanoparticles antagonize the effect of Cetuximab on head and neck squamous cell carcinoma in vitro. Issue 7 (3rd July 2017) - Gehrke, Thomas; Scherzad, Agmal; Ickrath, Pascal; Schendzielorz, Philipp; Hagen, Rudolf; Kleinsasser, Norbert; Hackenberg, Stephan
ABSTRACT: Zinc oxide nanoparticles (ZnO-NPs) are being used in many cosmetic products and have been shown to induce tumor-selective cell death in human head and neck squamous cell carcinoma (HNSCC) in vitro . Cetuximab is a monoclonal antibody directed against the epidermal growth factor receptor (EGFR), whose effectiveness for HNSCC, alone or in combination with cytostatic drugs, has been demonstrated intensively in the last decades. Nanoparticles are known to interact with protein structures and thus may influence their functionality. The aim of the current study was to evaluate the effect of ZnO-NPs on the antitumor properties of Cetuximab in HNSCC in vitro . Two HNSCC cell lines (FaDu and HLaC-78) were treated with 0.1, 1 or 10 μM Cetuximab as well as 0, 0.1 or 1 μg/ml ZnO-NP. Qualitative assessment of ZnO-NP was conducted via transmission electron microscopy (TEM) and immunofluorescence staining. Evaluation was done via the MTT-assay after 24, 48 and 72 hours of incubation with Cetuximab and ZnO-NPs. ZnO-NPs were shown to antagonize the anti-tumor effects of Cetuximab in a time-dependent as well as dose-dependent way. These findings suggest an inhibitory interaction of ZnO-NPs with Cetuximab, which warrants further investigation.